Optimisation of extraction method to obtain chitosan from squid pen - Ab. Hadi, Hazrina; Ab Salam, Mohd Ghazali (2016)
The shell or skeleton of the crustaceans were made of 30–40% protein, 30–50% calcium carbonate, and 20–30% chitin. Chitosan which is derived from the chitin is a linear polymer of α (1→4)-linked 2-amino-2-deoxy- β-D-glucopyranose. Chitosan has many potential applications due to its chemical and biological properties. Thus, this study is to identify the best effective method to extract chitosan from chitin Chitosan was obtained from the squid pen by the process of decalcification, deproteination and deacetylation. The raw squid pen was treated with 1N hydrochloric acid for decalcification. Next, it was soaked with 1M sodium hydroxide for deproteination. After that the squid pen treated with 40% sodium hydroxide for deacetylation. During deacetylation process, there are different temperatures of 70oC, 90oC, 75oC and 60oC were applied to the squid pen for different batches (batch 1, batch 2, batch 3 and batch 4 respectively). Characterization parameters such as Fourier Transform Infrared (FTIR) Spectroscopy, solubility, viscosity test and pH was conducted to identify the purity and degree of deacetylation of the extracted chitosan. The percentage of yield for batch 1, batch 2, batch 3 and batch 4 was 82.30%, 82.80%, 95.60% and 37.70% respectively. For the solubility test, all the batches of chitosan slightly soluble in glycerin but shows a good solubility in different concentration of acetic acid and acetic acid+glycerin. For pH test, the chitosan that solubilized in 1% acetic acid has pH 3 while chitosan that solubilized in 0.5% acetic acid has pH of 3-4. Meanwhile for viscosity test, batch 1, batch 2, batch 3 and batch 4 have viscosity of 1144.34cP, 771.52cP, 1247.90cP and 1812.30cP respectively. For FTIR characterization, the trend of the spectrum of extracted chitosan was the same as the spectrum of standard commercialized chitosan. All the extracted chitosan has stretches the bands at 1650cm-1 and 1320cm-1. The optimum method to extract the chitosan was found to be from batch 3 which reflected by giving highest yield of chitosan. In addition, the chitosan extracted from this method also found to have the highest solubility in acidic solvent, good viscosity and pH that suitable for formulation.